FUNCTIONAL-SEMANTIC AND PARADIGMATIC CHARACTERISTIC OF THE VERB ‘«TO FORCE» IN MODERN ENGLISH (Scientific journal of the Fergana State University, 2023)
The article deals with the investigation of the verb to force in modern linguistics. Besides that it has been investigated lexico-semantic meanings of the verb to force in the context.